MYPE, SOCIAL NETWORKS AND RECESSIVE CRISIS IN THE WORLD - Palomino Silva, Julio Andrés (2009)
The effect that has the current economic - financial global crisis, in our country, and the role that the micro must have and small enterprise inside this recessive context it’s fundamental, So use an approach of social nets is important to face to the current crisis, the limitations that the MYP E face and that prevent from exploiting their potential, they stem from their limited scale and their weak relations of joing and collaboration that might be replaced by the creation of networks that use the social preexisting assets. The conclusion of so interesting entail is that, in the current conditions of the world market, the association and coordination between the micro and small enterprises it is a vital need.